IMPLEMENTATION OF THE PLAN-DO-REVIEW-SHARE-HAPPY (PLANDORESH) PROJECT-BASED LEARNING MODEL IN TECHNICAL DRAWING SUBJECTS - Aftoni; Ekohariadi, Soeryanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Since 2021, the Ministry of Education, Culture, Research and Technology (Kemdikbudristek) of the Republic of Indonesia has implemented an independent curriculum for all levels of education in stages. The policy for implementing this curriculum, actually not much has changed from the previous curriculum (2013 curriculum). However, specifically Vocational High Schools (SMK) through the Directorate General of Vocational Education are directed at implementing the project-based learning model (PjBL) or teaching factory (tefa) in implementing the accelerated curriculum after Covid-19. Implementing this project-based learning model requires the right strategy in its implementation, plandaoresh is one of them. The aim of this study is to find out the comparison of learning outcomes for Technical Drawing subjects that apply the plandoresh strategy with other strategies. The research subjects were two groups of class XII students with machining engineering skills competency, each numbering 36 students. The research results show a significant comparison between the implementation of the plandoresh strategy and the non-plandoresh strategy with a significance figure of α < 0.05 (0.000 < 0.005) and t count > t table (5.839 > 2.021).